Fully Immersive Virtual Reality in Logistics Modelling and Simulation Education - Dario Ogrizović; Ana Perić Hadžić; Mladen Jardas (Promet - Traffic&Transportation, 2021)
With the increasing development and popularisation of information and communication technology, new challenges are posed to higher education in the modernisation of teaching in order to make education and training of students as effective as possible. It is therefore very important to develop and experiment with appropriate development tools, explore their benefits and effectiveness, and integrate them into existing learning strategies. The emergence of a computer-generated digital environment that can be directly experienced, actions that can determine what is happening in it, growth of technological characteristics, and decline in prices of virtual reality hardware leads to a situation that cannot be ignored. This paper investigated users' perceptions on the potential use of fully immersive virtual reality head-mounted displays in a discrete-event simulation of logistics processes. The dynamic nature of virtual environments requires active participation which causes greater engagement, motivation, and interest aided by interaction and challenges.